2021
DOI: 10.1007/s11433-020-1710-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring bulk and surface acoustic modes in diamond by angle-resolved Brillouin spectroscopy

Abstract: The acoustic modes of diamond not only are of profound significance for studying its thermal conductivity, mechanical properties and optical properties, but also play a determined role in the performance of high-frequency and high-power acoustic wave devices. Here we report the bulk acoustic waves (BAWs) and surface acoustic waves (SAWs) of single crystal diamond by using the angle-resolved Brillouin light scattering (BLS) spectroscopy. We identify two high-velocity surface skimming bulk waves, with sound velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The calculated in-plane phonon wavevector is q || = 0.0228 nm –1 . Two pronounced peaks are attributed to the shear-horizontal surface wave (SHW) and high-frequency pseudo-longitudinal wave (HFPLW). , The important observation is that the frequencies of these peaks decrease with an increasing boron doping concentration in diamond. The latter provides solid evidence for the phonon softening in the acoustic polarization branches.…”
Section: Results Of Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated in-plane phonon wavevector is q || = 0.0228 nm –1 . Two pronounced peaks are attributed to the shear-horizontal surface wave (SHW) and high-frequency pseudo-longitudinal wave (HFPLW). , The important observation is that the frequencies of these peaks decrease with an increasing boron doping concentration in diamond. The latter provides solid evidence for the phonon softening in the acoustic polarization branches.…”
Section: Results Of Measurementsmentioning
confidence: 99%
“…Brillouin–Mandelstam light scattering (BMS), also referred to as Brillouin light spectroscopy (BLS), is a nondestructive optical technique that has been used extensively to study acoustic phonons in different types of materials . This technique has been employed to examine the mechanical properties of different types of diamond, e.g., polycrystalline, smooth fine-grained, and single-crystal diamond grown by chemical vapor deposition (CVD) method. The prior studies reported the characteristics of bulk longitudinal acoustic (LA) and transverse acoustic (TA) phonons as well as the traveling surface acoustic waves (SAWs) along the high-symmetry crystallographic directions. , The elasticity coefficients of diamond were extracted from BMS data. A recent detailed study has used the angle-resolved BMS to find the properties of SAWs along different crystallographic directions in diamond . No BMS data on the effect of boron on bulk and surface acoustic phonons in boron-doped diamond have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations of Direction-Dependent Sound Velocities: Utilizing the resultant method, we obtained the velocities of the acoustic phonons traveling along <100> and <111> directions, as mentioned in Section 3.3. It is worth noting that Xie et al [42] stated that if υ ΓU was significantly different from υ ΓX , the existence of the ΓU path (Figure 5b) would lead the υ ΓX in Equation (2) to change with θ i (υ ΓX ¼ υ 0 þ βsinθ i ), where υ 0 is the value of υ ΓX when θ i ¼ 0 and β is a θ i -dependent parameter due to the contribution of υ ΓU . However, the fitting errors for the variables were relatively larger when including the contribution of the υ ΓU , compared with the fitting results without considering the contribution of the υ ΓU , which thus have been displayed in Figure 5c,d, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the sound velocity of a BAW propagating along an arbitrary direction, Xie et al proposed a resultant method to calculate the sound velocity by establishing the connection between the sound velocities of the acoustic phonons propagating along the high-symmetry axes in the first BZ and the phonon wave vector involved in the scattering, [42] which can also be applied to our work. For a given Bravais lattice, the first BZ and the corresponding irreducible wedge (IW) can be figured out.…”
Section: Assignment Of the Acoustic Modesmentioning
confidence: 99%
See 1 more Smart Citation